The third generation (UMTS) spectrum auction in Germany - Veronika Grimm; Frank Riedel; Elmar Wolfstetter (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
The third generation UMTS auction in Germany raised an enormous amount of revenue, and at the same time achieved a more competitive market structure than other UMTS auctions in Europe. The present paper explains the design of that auction, and presents a game theoretic explanation of observed events during the crucial phase of that auction, which have puzzled several observers. In addition, the paper evaluates the merit of the German UMTS auction design, relative to the English design, that was predominantly employed in Europe.
urn:nbn:de:kobv:11-10050415
Keywords: D43; D44; D45; H20; L13; 330; auctions; telecommunications; industrial organization; game theory